An evaluation of democratic attitudes of prospective teachers in the faculty of education and Non-Thesis Master's Programs - Gömleksiz, Mehmet Nuri; Kan, Ayşe Ülkü (T.C. Milli Egitim Bakanligi, 2008)
Democracy is a life and administration style which focuses on respect for human rights, individuals' freedom and participation the administration effectively. Developing democracy depends on developing democratic attitudes and behaviors of the individuals. The teachers have great role and importance on developing democratic attitudes and behaviors. From this perspective, the importance of training prospective teachers having democratic attitudes and behaviors can easily be seen. The main purpose of this study is to determine the democratic attitudes of prospective teachers enrolled in Faculty of Education and in Non-Thesis Master's Programs both in Social and Mathematics-Science Branches. "Democratic Attitude Scale" adapted into Turkish by Gözütok (1995) was used in the study. The results of the study reveal that there is a statistically significant difference among prospective teachers' democratic attitudes by departments, gender and educational levels of their parents. Democratic attitude scores of female prospective teachers were found higher than male prospective teachers in all groups. Prospective teachers' democratic attitude scores increase positively parallel to the increase of their parents' educational level Democratic attitude scores of prospective teachers in Education Faculty were found higher than those in Non-Thesis Master's Programs. Similarly, democratic attitudes of prospective teachers in Non-Thesis Master's program in Social Branches are higher than those in Non-Thesis Master's Program in Science and Mathematics Branches. On the other hand, no significant differences were found between the groups by their parents' economic levels.
E?itim fakültesi ve tezsiz yüksek lisans programlarina kayitli ü?retmen adaylarinin demokratik tutumlarinin de?erlendirilmesi (Fırat Üniversitesi Örne?i)
Keywords: Democracy; Democratic attitudes; Democratic attitudes scale; Procpective teachers